1999
DOI: 10.2486/indhealth.37.329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mineral Fibers on the Gene Expression of Proinflammatory Cytokines and Inducible Nitric-Oxide Synthase in Alveolar Macrophages.

Abstract: To determine which parameters are useful for the risk assessment of man-made mineral fibers (MMMFs), we examined the gene expression of interleukin-la (IL-1a), tumor necrosis factor a (TNFa), interleukin-6 (IL-6) and inducible nitric-oxide synthase (iNOS) in mineral fiber-exposed alveolar macrophages (AMs). Male Wistar rats were intratracheally exposed to saline or mineral fibers suspended in saline (2 mg of crocidolite, chrysotile, alumina silicate refractory fiber (RF1) or potassium octatitanate whisker (TW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…In this study, we used a concentration of 2 mg since in our previous long-term fiber inhalation study we found the maximum amount of dust deposited in the lung to be 2 mg regardless of the fiber type (Oyabu et al, 1997). In a further study we also demonstrated a correlation between the fibrotic potential of 4 types of fibers and the expression of fibrosis-related genes after the instillation of a 2-mg dose (Morimoto et al, 1999. Therefore, the dose instilled in the present study was the upper limit of the amount physiologically deposited in the lung.…”
Section: Discussionmentioning
confidence: 75%
“…In this study, we used a concentration of 2 mg since in our previous long-term fiber inhalation study we found the maximum amount of dust deposited in the lung to be 2 mg regardless of the fiber type (Oyabu et al, 1997). In a further study we also demonstrated a correlation between the fibrotic potential of 4 types of fibers and the expression of fibrosis-related genes after the instillation of a 2-mg dose (Morimoto et al, 1999. Therefore, the dose instilled in the present study was the upper limit of the amount physiologically deposited in the lung.…”
Section: Discussionmentioning
confidence: 75%
“…In lung injury caused by dusts, phagocytosis of the dust induces inflammation via free radicals, and persistent or progressive inflammation is likely to cause fibrosis and, in turn, tumors (Borm & Driscoll, 1996;Kim et al, 2007;Morimoto et al, 1999). Continued inflammation has been reported in an animal exposure model using asbestos and silica, and thus persistent inflammation is an important pathology in the formation of irreversible chronic lesions (Borm et al, 1996;Shacter & Weitzman, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…Die chronische Entzündung wird als treibender Prozess für weitere pathophysiologische Zell und Gewebever änderungen der Lunge angesehen (IARC 2002;ILSI 2005;NTP 2010). Die Schädi gung der Epithelzellen führt zu Hyperplasie und Hypertrophie und gelegentlich zu Tumorentstehung (Driscoll et al1995;Mossman und Churg 1998;Oberdörster und Lehnert 1991;Saffiotti 1998;Tsuda et al 1997 (Bermudez et al 2003;Creutzenberg et al 1997;IARC 2002;Morimoto et al 1999Morimoto et al , 2001NTP 2010;Schürkes et al 2004). Auch KohlenstoffNanoröhrchen induzieren chronische Entzündung bei den exponierten Tieren (Poland et al 2008).…”
Section: Chronische Entzündungunclassified